Exploring students’ communication skills through sales learning in junior high schools - Amelia; Anada, Azwar; Montessori, Maria (Universitas Jambi, Indonesia, 2025)
This research aims to describe improving students' communication skills by combining the syntax of the Gallery Walk and Two Stay Two Stray learning models, hereinafter referred to as sales learning. This research is quantitative with a quasi-experimental approach. Data collection methods included observation sheets, communication skills and data analysis of communication skills improvements using the TCR formula and t-test results. The results showed that the TCR score of the experimental class was 76.92, and the TCR of the control class was 59.19. The results of this research indicate a significant increase in communication skills for students who study sales learning compared to students who do not use sales learning. Communication skills are described in several indicators, namely, the ability to convey opinions, the ability to listen to opinions, the ability to provide appropriate responses, the ability to encourage other group members to participate in expressing their opinions, and the ability to resolve conflicts.